2006
DOI: 10.3844/ajassp.2006.1790.1794
|View full text |Cite
|
Sign up to set email alerts
|

On Concircular Structure Spacetimes II

Abstract: We studied concircular structure spacetimes which are connected 4-dimensional Lorentzian concircular structure manifolds.2000 Mathematics subject classification: 53C40, 53C50, 53C80

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Then Shaikh and Baishya ( [26], [27]) investigated the applications of (LCS) n -manifolds to the general theory of relativity and cosmology. The (LCS) nmanifolds is also studied by Atceken [2], Hui and Atceken [16], Shaikh [25], Shaikh and Binh [31], Shaikh and Hui [32], Sreenivasa, Venkatesha and Bagewadi [33] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Then Shaikh and Baishya ( [26], [27]) investigated the applications of (LCS) n -manifolds to the general theory of relativity and cosmology. The (LCS) nmanifolds is also studied by Atceken [2], Hui and Atceken [16], Shaikh [25], Shaikh and Binh [31], Shaikh and Hui [32], Sreenivasa, Venkatesha and Bagewadi [33] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Further, if (∇ X )(Y, Z) 0 for all X, Y, Z ∈ χ(M), then∇ is said to be a quarter symmetric non-metric connection. Lorentzian concircular structure manifolds (briefly, (LCS) n -manifolds) introduced in [29] as a generalisation of LP-Sasakian manifold [25], has many applications in the general theory of relativity and cosmology ( [32], [33]). In [23] it has shown that LCSspacetimes coincide with generalised Robertson-Walker spacetimes.…”
Section: Introductionmentioning
confidence: 99%
“…As a generalization of LP-Sasakian manifold, Shaikh [13] recently introduced the notion of Lorentzian concircular structure manifolds (briefly, (LCS) n -manifolds) with an example. Such manifolds have many applications in the general theory of relativity and cosmology ( [15], [16]).…”
Section: Introductionmentioning
confidence: 99%